2021
DOI: 10.1021/acsami.1c05833
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent, Stretchable, and Conducting Ionoelastomers Based on Poly(ionic liquid)s

Abstract: The rapid development of soft electronics has revitalized the research of conducting elastomers. However, the design of conducting elastomers having high stretchability and good transparency still remains a considerable challenge. In this study, we develop a highly transparent, stretchable, and conducting ionoelastomer based on a poly­(ionic liquid) in which cations are fixed to a stretchable elastomeric network and counter anions are mobile. The ionoelastomer solves the dilemma of simultaneous transparency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 53 publications
0
52
0
Order By: Relevance
“…1-Hydroxycyclohexyl phenyl ketone (photoinitiator 184, 98%, Aladdin) and 2,2,3,4,4,4-hexafluorobutyl acrylate (HFBA, 96%, Shang Fluoro) were used as received. 1-(6-(Acryloyloxy)-hexyl)-3-ethylimdazolium bis­(trifluomethylsulfonyl)­imide ([EIC 6 A]­[TFSI]) was synthesized as previously described . Acetone (99%, Guangzhou Chemical) and deionized water (18.2 MΩ·cm, Millipore) were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-Hydroxycyclohexyl phenyl ketone (photoinitiator 184, 98%, Aladdin) and 2,2,3,4,4,4-hexafluorobutyl acrylate (HFBA, 96%, Shang Fluoro) were used as received. 1-(6-(Acryloyloxy)-hexyl)-3-ethylimdazolium bis­(trifluomethylsulfonyl)­imide ([EIC 6 A]­[TFSI]) was synthesized as previously described . Acetone (99%, Guangzhou Chemical) and deionized water (18.2 MΩ·cm, Millipore) were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…1-(6-(Acryloyloxy)-hexyl)-3-ethylimdazolium bis(trifluomethylsulfonyl)imide ([EIC 6 A][TFSI]) was synthesized as previously described. 33 Acetone (99%, Guangzhou Chemical) and deionized water (18.2 MΩ•cm, Millipore) were used without further purification. Electroluminescent phosphor ZnS:Cu and ZnS:Mn microparticles were purchased from Shanghai Keyan.…”
Section: Methodsmentioning
confidence: 99%
“…Such performance is achieved by infusing poly(acrylic acid) (PAA) with an ionic liquid. A similar concept of using ionogels to control DEA through ionic signals was also reported by Ming et al [50]. More recently, Shi et al reported ionic signal transmission in harsh environments by synthesizing an ionogel conductor using poly(ethyl acrylate) as the underlying polymer network [51].…”
Section: Signal Transmissionmentioning
confidence: 63%
“…First, lithium ionic (Li + ) salt-based SICs have been investigated. 32,[110][111][112][113][114] The ionic conduction of Li + can be facilitated by hopping or chain segmental motion of the ethylene oxide chains. 115 Studies have attempted to design the polymers in two ways based on whether the ethylene oxide groups are incorporated into the side-chain or the main chain (Fig.…”
Section: Liquid-free Sicsmentioning
confidence: 99%
“…Ding et al reported ionic-conducting elastomers composed of copolymers of n -butyl acrylate (BA) and oligoethylene glycol methyl ether acrylates (OEGMEA), and Li + TFSI − . 110 The BA and OEGMEAs provide elastomeric properties and lower T g , thus enabling ionically conductive without liquids (Fig. 10b).…”
Section: Stretchable Ionic Conductors (Sics)mentioning
confidence: 99%